Jalan Tuanku Abdul Rahman : its development and emergence as one of the prime commercial areas in Kuala Lumpur - 178260 Tay, Tam
This dissertation is a study of Jalan Tuanku Abdul Rahman --- its development, its success and its short-comings as a commercial area. The first part traces the early development of Jalan Tuanku Abdul Rahman and the initial pattern of growth. Reasons for its popularity and the resultant features of land use are also treated here. The second describes the situation today. It attempts to analyse certain characteristics peculiar to this street and the circumstances leading to them. It also seeks to relate these characteristics to land use and forms of development. In the final part, a conclusion in drawn as to the degree of success of Jalan Tuanku Abdul Rahman as a commercial centre. It also offers a glimpse into the future. How will Jalan Tuanku Abdul Rahman be like in the future taking into consideration the various short-comings and problems being faced today? Will it continue to progress or wil1 it decline into a secondary commercial area as many areas in the citycentre do?